Heterogeneous uptake of 18F-FDG and 18F-PSMA-1007 PET/CT in lung cancer and lymph node metastasis - Yuan Hu; Peng Wang; Wenli Dai (BMC Pulmonary Medicine, 2023)
Abstract Background PSMA PET/CT has shown excellent results in imaging of prostate cancer. However, some nonprostatic malignancies can also demonstrate 18 F-PSMA uptake, including primary lung cancer. 18 F-FDG PET/CT is widely employed in initial staging, response to therapy and follow-up assessment for lung cancer. Here we present an interesting case report on the different patterns of PSMA and FDG uptake between primary lung cancer and metastatic intrathoracic lymph node metastases in a patient with concurrent metastatic prostate cancer. Case presentation A 70-year-old male underwent 18 F-FDG PET/CT and 18 F-PSMA-1007 PET/CT imaging due to suspicion primary lung cancer and prostate cancer. The patient eventually was diagnosed with non-small cell lung cancer (NSCLC) with mediastinal lymph node metastases and prostate cancer with left iliac lymph node and multiple bone metastases. Interestingly, our imaging revealed different patterns of tumor uptake detected on 18 F-FDG and 18 F-PSMA-1007 PET/CT in primary lung cancer and lymph node metastases. The primary lung lesion showed intense FDG uptake, and mild uptake with 18 F-PSMA-1007. Whereas the mediastinal lymph node metastases showed both intense FDG and PSMA uptake. The prostate lesion, left iliac lymph node, and multiple bone lesions showed significant PSMA uptake and negative FDG uptake. Conclusion In this case, there was a homogeneity of 18 F-FDG intense uptake between LC and metastatic lymph nodes, but a heterogeneity in 18 F-PSMA-1007 uptake. It illustrated that these molecular probes reflect the diversity of tumor microenvironments, which may help us understand the differences of the tumor response to treatment.